2014
DOI: 10.1016/j.scitotenv.2013.12.073
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical behaviour of rare earths in Vitis vinifera grafted onto different rootstocks and growing on several soils

Abstract: The geochemical behaviour of lanthanides and yttrium (Rare Earth Elements, REEs) has been investigated mainly in geological systems where these elements represent the best proxies of processes involving the occurrence of an interface between different media. This behaviour is assessed according to features recorded in sequences of REE concentrations along the REE series normalised with respect to a reference material. In this study, the geochemical behaviour of REE was investigated in different parts of Vitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 71 publications
6
39
0
Order By: Relevance
“…are reported in Figs. 1-4 Censi et al, 2014). The standard deviations values found among the soil samples reflect the good spatial homogeneity of the studied area, confirming the hypothesis of the ''similar soil", in the YLOID distribution, experienced by the different roots of the different grapevines (grafting combination) in vineyard.…”
Section: Soilsupporting
confidence: 80%
See 1 more Smart Citation
“…are reported in Figs. 1-4 Censi et al, 2014). The standard deviations values found among the soil samples reflect the good spatial homogeneity of the studied area, confirming the hypothesis of the ''similar soil", in the YLOID distribution, experienced by the different roots of the different grapevines (grafting combination) in vineyard.…”
Section: Soilsupporting
confidence: 80%
“…Investigating lanthanoids and yttrium distributions in V. vinifera, most of data were treated according to a ''classical" approach of a multivariate data analysis (Aceto et al, 2013;Bertoldi et al, 2011). In a relatively recent paper (Censi, Saiano, Pisciotta, & Tuzzolino, 2014), it has been demonstrated that YLOID patterns of aerial parts of three different rootstocks grown off-soil, were a suitable geochemical proxy, even if biological substrata (roots, vine shoots, leaves, etc.) are involved, of three soils of different nature.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The potential effect of REE+Y on plant growth and their mechanisms for entering into biomass is of growing interest, particularly the uptake, distribution and accumulation of REE+Y in plants (Wyttenbach et al 1998;Tyler 2004;Tyler & Olsson 2005;Brioschi et al 2013;Wen et al 2001;Fu et al 2001;Censi et al 2014;Miao et al 2008;Miao et al 2011;Lima e Cunha et al 2014;Ding et al 2006;Hu et al 2006). Despite this, the REE+Y content of wild-growing plants in natural ecosystems is much less studied.…”
Section: Ree+y Translocation To Plantsmentioning
confidence: 99%
“…According to the consortia regulation all wines analysed are made by the Cesanese red grape variety (monocultivar); this ensure from possible differential elemental uptake from soil via the vine roots as seen to occur for REE (Censi et al, 2014).…”
mentioning
confidence: 99%